Validity of the modified RULA for computer workers and reliability of one observation compared to six. - Levanon, Yafa; Lerman, Yehuda; Gefen, Amit; Ratzon, Navah Z. (Ergonomics, 2014)
Awkward body posture while typing is associated with musculoskeletal disorders (MSDs). Valid rapid assessment of computer workers' body posture is essential for the prevention of MSD among this large population. This study aimed to examine the validity of the modified rapid upper limb assessment (mRULA) which adjusted the rapid upper limb assessment (RULA) for computer workers. Moreover, this study examines whether one observation during a working day is sufficient or more observations are needed. A total of 29 right-handed computer workers were recruited. RULA and mRULA were conducted. The observations were then repeated six times at one-hour intervals. A significant moderate correlation (r = 0.6 andr = 0.7 for mouse and keyboard, respectively) was found between the assessments. No significant differences were found between one observation and six observations per working day. The mRULA was found to be valid for the assessment of computer workers, and one observation was sufficient to assess the work-related risk factor. Practitioner Summary: This study approved the validity of the mRULA for assessing computer workers and the reliability of one observation in comparison with six. This version identified a greater percentage of computer workers at a higher ergonomic risk level and therefore may encourage clinicians to use the mRULA for assessment.